'We have got the tools': Qualitative evaluation of a mental health Wellness Recovery Action Planning (WRAP) education programme in Ireland. Issue 3 (1st April 2013) - Keogh, B.; Higgins, A.; DeVries, J.; Morrissey, J.; Callaghan, P.; Ryan, D.; Gijbels, H.; Nash, M.
<x xml:space="preserve">Abstract</x> Accessible summary Because Recovery is an important idea, an educational course was run to help service users and professionals to introduce Wellness Recovery Action Planning (WRAP) to interested parties in their communities. The evaluation of this course made use of group interviews in which participants were asked about their experiences on the course. Although they enjoyed the course and were positive about Recovery and WRAP, they felt that they still lacked confidence in the presentation skills that they felt they required. Abstract In recent years, there has been a consistent drive to incorporate Recovery principles into the Irish mental health services. A group of Irish mental health service providers came together and delivered a 5‐day Wellness Recovery Action Planning (WRAP) facilitator's programme. The programme was developed and delivered by key stakeholders including people with self‐experience of mental health problem. This paper presents the qualitative findings from an evaluation of these facilitator's programmes. Three focus groups were held with 22 people, the majority of who described themselves as mental health professionals and/or people with self‐experience of mental health problems. Data were analysed using a thematic approach and yielded four themes. Although the participants were positive about the programme and felt that their knowledge of Recovery and WRAP had improved, they felt that they still lacked confidence in terms of the presentation skills required for facilitating Recovery and WRAP programmes. The findings suggest that mental health service providers who wish to develop service users and clinicians as WRAP facilitators need to put more emphasis on the provision of facilitation and presentation skills in the programmes they develop.